Composite anti-freezing microwave modified polymer dust suppressant as well as preparation method and application thereof
By preparing a composite antifreeze-type microwave-modified polymer dust inhibitor, combined with sodium alginate, sodium carboxymethyl starch and other modifiers, the problem that existing dust inhibitors are difficult to have wind corrosion, water retention and antifreeze properties at the same time, achieving efficient coal dust prevention and control effects.
Patent Information
- Application Number
- CN202510016642.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-22
AI Technical Summary
On the basis of improving the wetting effect, existing dust inhibitors are difficult to have wind corrosion, water retention and anti-freeze properties at the same time, and cannot effectively solve the health, explosion and environmental pollution caused by coal dust in coal mines.
By preparing a composite antifreeze-type microwave-modified polymer dust inhibitor, sodium alginate and sodium carboxymethyl starch are used as raw materials, combined with carboxymethyl chitosan, calcium chloride and ammonium dodecyl sulfate, the viscosity and wettability of the dust inhibitor are improved through graft copolymerization modification and microwave reaction technology.
It has achieved efficient wetting, good water retention, wind corrosion and anti-freeze properties of dust inhibitors, significantly improved the coal dust prevention and control effect, and reduced the health and environmental risks caused by coal dust in coal mines.
Smart Images

Figure CN119859506A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of dust suppressants, in particular to a composite antifreeze type microwave modified polymer dust suppressant and a preparation method and application thereof. Background Art
[0002] Coal occupies a dominant position in China's energy consumption structure and will continue to maintain this position in the foreseeable future. With the high-intensity mining of shallow coal mines and the further increase in mining depth, the problems of worker health, coal dust explosion and environmental pollution caused by coal dust have become more and more serious. By the end of 2023, China has reported a total of 931,000 cases of occupational pneumoconiosis patients, and the water, air and soil pollution caused by excessive coal dust are countless. How to achieve safe and environmentally friendly production in coal mines has become the focus of public attention. How to efficiently use dust suppressants to remove dust has always been an important direction in the field of research on coal mine dust safety prevention and control, and how to improve the composite properties of dust suppressants themselves is an important topic in this research direction. At present, the research reports on dust suppressants in the prior art mainly include: CN104087251A discloses a coal dust inhibitor characterized by 10-20% disodium lauryl polyoxyethylene ether sulfosuccinate, 10-20% dodecyl dimethyl betaine, and 70-80% water, which has a good wetting effect. CN108795385A discloses a composite dust suppressant, which uses 5% oxidized starch and 1% polyvinyl alcohol as the main raw materials for synthesizing the inhibitor, 93.5% water as a solvent, 0.005% potassium permanganate as an oxidant, and 0.5% borax as a cross-linking agent to prepare a composite coal dust suppressant with good bonding and water retention. It can be seen that the above inventions do not have efficient antifreeze and anti-wind erosion properties on the basis of good wetting effect of coal dust.
[0003] Therefore, it is of great significance to develop a mining dust suppressant that has high efficiency in wetting and moisturizing as well as anti-wind erosion and antifreeze properties. Summary of the invention
[0004] In order to solve the above technical problems, the object of the present invention is to provide a composite antifreeze type microwave modified polymer dust suppressant and a preparation method and application thereof.
[0005] To achieve the above objectives, the present invention is implemented by the following technical scheme: A method for preparing a composite antifreeze type microwave modified polymer dust suppressant, characterized in that it is prepared according to the following steps:
[0006] (1) placing sodium alginate and sodium carboxymethyl starch in a container, heating them to uniformly disperse them in water, adding tert-butyl hydroperoxide solution, stirring, then adding N,N′-methylenebisacrylamide and acrylamide, placing the container in a microwave reactor, stirring and heating to react to obtain a uniform and stable sodium alginate-sodium carboxymethyl starch mixed solution;
[0007] (2) cooling the sodium alginate-sodium carboxymethyl starch mixed solution, adding carboxymethyl chitosan and ammonium dodecyl sulfate, stirring thoroughly, adding calcium chloride, and mixing to obtain a composite antifreeze type microwave modified polymer dust suppressant.
[0008] In the above scheme: in the composite antifreeze type microwave modified polymer dust suppressant reaction liquid, the mass concentration of sodium alginate is 0.25-0.45%, the mass concentration of sodium carboxymethyl starch is 0.05-0.09%, the mass concentration of tert-butyl hydroperoxide is 0.03-0.06%, the mass concentration of N,N′-methylenebisacrylamide is 0.02-0.03%, the mass concentration of acrylamide is 0.32-0.53%, the mass concentration of carboxymethyl chitosan is 0.19-0.39%, the mass concentration of calcium chloride is 0.62-1.17%, and the mass concentration of ammonium dodecyl sulfate is 0.02-0.03%.
[0009] In the above scheme, the mass ratio of sodium alginate and sodium carboxymethyl starch is 5:1.
[0010] In the above scheme: the mass percentage content of tert-butyl hydroperoxide in the tert-butyl hydroperoxide solution is 30%.
[0011] In the above scheme: in step (1), the temperature of heating and dispersing is 60-70°C.
[0012] In the above scheme: the microwave reactor is set to a reaction temperature of 40-50°C and a reaction time of 30-40 minutes.
[0013] In the above scheme: after adding the tert-butyl hydroperoxide solution, stir for 20-30 minutes.
[0014] A composite antifreeze type microwave modified polymer dust suppressant prepared by the preparation method of the composite antifreeze type microwave modified polymer dust suppressant.
[0015] The composite antifreeze type microwave modified polymer dust suppressant is used in the prevention and control of coal dust in the mining process.
[0016] The sodium alginate and sodium carboxymethyl starch of the present invention are derived from Sargassum and potato starch, which are not only environmentally friendly but also can be used as raw materials for graft copolymerization. After the sodium alginate and sodium carboxymethyl starch are used as raw materials for graft copolymerization modification, the viscosity of the dust suppressant can be increased, and the wind erosion resistance of the dust suppressant can be effectively improved. Carboxymethyl chitosan can provide a good moisturizing effect as a water retaining agent, and calcium chloride as a commonly used antifreeze agent not only provides efficient antifreeze properties, but also has an excellent synergistic wetting effect with ammonium dodecyl sulfate, and has an excellent wetting effect. The problem that the dust suppressant cannot have wind erosion resistance, high water retention and antifreeze properties at the same time is solved.
[0017] Sodium alginate-sodium carboxymethyl starch polymer is a modification method based on graft copolymerization, wherein sodium alginate and sodium carboxymethyl starch are used as modification raw materials, tert-butyl hydroperoxide is used as a polymerization initiator, N,N′-methylenebisacrylamide is used as a crosslinking agent, and acrylamide is used as a reaction monomer for preparation. The carboxymethyl chitosan is used as a water retaining agent to provide a long-lasting moisturizing effect. Calcium chloride is used as an antifreeze agent and an inorganic salt auxiliary agent of ammonium dodecyl sulfate to provide antifreeze performance, and combined with ammonium dodecyl sulfate, it can also provide excellent wetting properties.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] (1) The dust suppressant prepared by the present invention uses sodium alginate and sodium carboxymethyl starch as raw materials. Sodium alginate and sodium carboxymethyl starch are taken from Sargassum and potato starch, which meet environmental protection requirements. In addition, the initiator, cross-linking agent and reaction monomer used in the preparation process of sodium alginate-carboxymethyl starch polymer have no toxic reaction to the human body and are usually non-irritating to human skin.
[0020] (2) The composite antifreeze type microwave modified polymer dust suppressant prepared by the present invention can increase the viscosity of the dust suppressant after the sodium alginate and sodium carboxymethyl starch are grafted and copolymerized, and effectively improve the wettability of the dust suppressant. Combined with the water retaining agent carboxymethyl chitosan, it also has a good moisturizing effect.
[0021] (3) The composite antifreeze type microwave modified polymer dust suppressant prepared by the present invention has a relatively high viscosity, which allows the coal dust particles to adhere to each other, forming a protective shell with a certain consolidation strength on the surface of the coal dust, and has anti-wind erosion performance.
[0022] (4) The composite antifreeze type microwave modified polymer dust suppressant prepared by the present invention has antifreeze properties due to the addition of antifreeze calcium chloride. At the same time, calcium chloride, as an inorganic salt auxiliary agent of ammonium dodecyl sulfate, has a better synergistic wetting effect with ammonium dodecyl sulfate. The counter ions produced by calcium chloride ionization reduce the electrostatic repulsion between the hydrophilic groups of ammonium dodecyl sulfate, making the aggregation arrangement at the gas-liquid interface more compact and orderly, thereby obtaining a better wetting effect.
[0023] (5) The dust suppressant prepared by the present invention is simple to prepare, the raw materials are economical, and it has good social and economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is the wind erosion rate of coal dust at different wind erosion times after spraying water and the dust suppressant of Examples 1-3.
[0025] Figure 2 It is the moisture content of coal dust at different times after spraying water and the dust suppressant of Examples 1-3.
[0026] Figure 3 It is the ratio of the surface tension decrease of the dust suppressant solution after adding different inorganic salt additives. DETAILED DESCRIPTION
[0027] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.
[0028] Example 1
[0029] Preparation of composite antifreeze type microwave modified polymer dust suppressant:
[0030] The mass concentration of each component in the reaction liquid of the composite antifreeze type microwave modified polymer dust suppressant is: 0.25% sodium alginate, 0.05% sodium carboxymethyl starch, 0.03% tert-butyl hydroperoxide, 0.02% N,N′-methylenebisacrylamide, 0.32% acrylamide, 0.19% carboxymethyl chitosan, 0.62% calcium chloride and 0.02% dodecyl ammonium sulfate, and the balance is water.
[0031] Sodium alginate and sodium carboxymethyl starch are placed in a three-necked flask with a capacity of 500 ml. Under a water bath condition of 60-70° C., the raw materials are uniformly dispersed in water. Tert-butyl hydroperoxide solution (the mass concentration of tert-butyl hydroperoxide is 30%) is added to the three-necked flask. After stirring for 20 minutes, N, N′-methylenebisacrylamide and acrylamide are added to the three-necked flask. Then, the three-necked flask is slowly placed in a microwave reactor for fixing. The reaction temperature of the microwave reactor is set to 40° C. The reaction is carried out under magnetic stirring at 80 r / min for 40 minutes to obtain a uniform and stable sodium alginate-sodium carboxymethyl starch mixed solution. After cooling, carboxymethyl chitosan and ammonium dodecyl sulfate are added to the sodium alginate-sodium carboxymethyl starch mixed solution, which is fully stirred. Finally, calcium chloride is added to fully mix the sample to obtain a composite antifreeze type microwave modified polymer dust suppressant.
[0032] Example 2
[0033] Preparation of composite antifreeze type microwave modified polymer dust suppressant:
[0034] The mass concentration of each component in the reaction liquid of the composite antifreeze type microwave modified polymer dust suppressant is: 0.35% sodium alginate, 0.07% sodium carboxymethyl starch, 0.05% tert-butyl hydroperoxide, 0.026% N,N′-methylenebisacrylamide, 0.44% acrylamide, 0.30% carboxymethyl chitosan, 0.95% calcium chloride and 0.024% dodecyl ammonium sulfate, and the balance is water.
[0035] Sodium alginate and sodium carboxymethyl starch are placed in a three-necked flask with a capacity of 500 ml. Under a water bath condition of 60-70° C., the raw materials are uniformly dispersed in water. Tert-butyl hydroperoxide solution (the mass concentration of tert-butyl hydroperoxide is 30%) is added to the three-necked flask. After stirring for 30 minutes, N, N′-methylenebisacrylamide and acrylamide are added to the three-necked flask. Then, the three-necked flask is slowly placed in a microwave reactor for fixing. The reaction temperature of the microwave reactor is set to 45° C. The reaction is carried out under magnetic stirring at 90 r / min for 35 minutes to obtain a uniform and stable sodium alginate-sodium carboxymethyl starch mixed solution. After cooling, carboxymethyl chitosan and ammonium dodecyl sulfate are added to the sodium alginate-sodium carboxymethyl starch mixed solution, which is fully stirred. Finally, calcium chloride is added to fully mix the sample to obtain a composite antifreeze type microwave modified polymer dust suppressant.
[0036] Example 3
[0037] Preparation of composite antifreeze type microwave modified polymer dust suppressant:
[0038] The mass concentration of each component in the reaction liquid of the composite antifreeze type microwave modified polymer dust suppressant is: 0.45% sodium alginate, 0.09% sodium carboxymethyl starch, 0.06% tert-butyl hydroperoxide, 0.03% N,N′-methylenebisacrylamide, 0.53% acrylamide, 0.39% carboxymethyl chitosan, 1.17% calcium chloride and 0.03% dodecyl ammonium sulfate, and the balance is water.
[0039] Sodium alginate and sodium carboxymethyl starch are placed in a three-necked flask with a capacity of 500 ml. Under a water bath condition of 60-70° C., the raw materials are uniformly dispersed in water. Tert-butyl hydroperoxide solution (the mass concentration of tert-butyl hydroperoxide is 30%) is added to the three-necked flask. After stirring for 20 minutes, %N,N′-methylenebisacrylamide and acrylamide are added to the three-necked flask. Then, the three-necked flask is slowly placed in a microwave reactor for fixing. The reaction temperature of the microwave reactor is set to 50° C. The reaction is carried out under magnetic stirring at 100 r / min for 40 minutes to obtain a uniform and stable sodium alginate-sodium carboxymethyl starch mixed solution. After cooling, carboxymethyl chitosan and ammonium dodecyl sulfate are added to the sodium alginate-sodium carboxymethyl starch mixed solution, which is fully stirred. Finally, calcium chloride is added to fully mix the sample to obtain a composite antifreeze type microwave modified polymer dust suppressant.
[0040] Determination of the dust suppression ability of the dust suppressants prepared in Examples 1-3
[0041] The surface tension of the solution of Example 1-3 was tested using a ZTZL2000 surface tension meter;
[0042] Table 1 Surface tension test results
[0043]
[0044] The dust suppressants prepared in Examples 1-3 were applied on site, and the dust concentrations were measured when no dust prevention measures were taken on the working surface, when only clean water spraying was used, and when clean water was added with Examples 1-3 of the present invention and then sprayed, as shown in Table 2.
[0045] Table 2 Dust concentration at different work locations
[0046]
[0047]
[0048] It can be seen from Table 2 that after applying the dust suppressant prepared by Examples 1-3, the average dust reduction rates of total dust and respirable dust on the working surface increased by 32.651% and 23.91%, 27.35 and 21.75%, and 26.62% and 19.83% respectively compared with clean water. The dust reduction efficiency is improved, which is a great improvement.
[0049] Determination of the anti-wind erosion performance of the dust suppressants prepared in Examples 1-3
[0050] First, equal amounts of coal powder were placed on different flat plates and naturally piled to form a coal pile; secondly, the dust suppressant prepared in Examples 1-3 was evenly sprayed on the surface of the coal pile using a spray pot, and clean water was sprayed on the coal pile as a control group. Finally, a blower was used to simulate natural wind erosion of a completely naturally dried coal pile, which was treated for 2 hours, and the weight was measured every 30 minutes, and then the wind erosion rate was calculated. The wind erosion rate was calculated according to the equation.
[0051] Wind erosion rate formula: K = (G-G0) / G×100%
[0052] Where: K is the wind erosion rate of coal powder, G is the initial mass of coal powder, g; G0 is the mass of coal powder after wind erosion, g.
[0053] The results are as follows Figure 1 As shown, it is shown that after spraying the dust suppressant solution prepared in Examples 1-3, the wind erosion rate is significantly reduced compared with that of spraying with clean water. It can be seen that after 2 hours of wind erosion, the wind erosion rate of spraying with clean water is 54.1%, while the wind erosion rates after spraying the dust suppressant solution prepared in Examples 1-3 are 3.8%, 4.5%, and 4.7%, respectively, indicating that the prepared composite antifreeze type microwave modified polymer dust suppressant has good anti-wind erosion performance.
[0054] Determination of the water retention performance of the dust suppressants prepared in Examples 1-3
[0055] Take 3.0 grams of 200-mesh coal powder and put it in four culture dishes, spray 20 ml of water and 20 ml of the dust suppressant solution prepared in Examples 1-3 respectively, place it in a constant temperature drying oven, set the temperature to 30°C and measure for 24 hours, measure a set of data every 4 hours, and finally calculate the moisture content of the coal powder after being moistened with water and the dust suppressant solution prepared in Examples 1-3.
[0056] The formula for calculating moisture content is: α = (M2-M1) / M2×100%;
[0057] In the formula: M2-initial coal powder mass; M1-coal powder mass after 24h; ɑ-moisture content of coal powder (%).
[0058] The results are as follows Figure 2 As shown, the moisture content of the coal powder sprayed with the dust suppressant solution prepared in Examples 1-3 all decreased slowly, and the water retention was strong. The 24h moisture content was 6.54%, 6.59%, and 6.65% respectively, while the moisture content of the coal powder sprayed with water was only 1.5%. Therefore, the dust suppressant has a strong water retention performance, and the water retention rate can still reach 95% after spraying the dust suppressant solution at 35°C for 24h.
[0059] Determination of the antifreeze performance of the dust suppressants prepared in Examples 1-3
[0060] 1 kg of 20-mesh coal powder was spread on four trays of the same specifications, and 100 ml of water, 100 ml of the dust suppressant solution prepared in Examples 1-3, and 100 ml of the dust suppressant solution without antifreeze (Example 4) were sprayed on them respectively, and placed in a -30°C refrigerator for 3 hours. When the coal could be poured out after being taken out, it was considered that the antifreeze effect was achieved. The experimental results are shown in Table 3.
[0061] Table 3 Antifreeze test results
[0062]
[0063] It can be seen from the results in Table 3 that after being frozen at -30°C for 3 hours, the coal powder sprayed with the dust suppressant solution prepared in Examples 1-3 can be poured out, indicating that a good antifreeze effect has been achieved. However, after spraying water and the dust suppressant solution without antifreeze, the coal dust is frozen and solidified, and has no antifreeze effect.
[0064] Determination of the effect of adding different inorganic salt additives on the wetting effect of composite antifreeze type microwave modified polymer dust suppressant
[0065] On the basis of Example 2, the surface tension of sodium chloride, sodium bicarbonate, aluminum chloride, and sodium phosphate was measured using a ZTZL2000 surface tension meter, and the surface tension after calcium chloride was removed was measured. Based on the surface tension of the composite antifreeze type microwave modified polymer dust suppressant solution after calcium chloride was removed, a graph of the average decrease in the surface tension of the dust suppressant solution after the addition of five inorganic salt additives was drawn, as shown in FIG. Figure 3 shown.
[0066] from Figure 3 It can be seen that compared with the dust suppressant solution without inorganic salt additives, the dust suppressant solution with calcium chloride has the largest decrease in surface tension, which is 15.23%, while the dust suppressant solution with sodium chloride, aluminum chloride and sodium phosphate has a relatively low decrease in surface tension. The addition of sodium bicarbonate even resulted in an increase in surface tension, which indicates that the counterions ionized by calcium chloride in the solution can more directly and effectively reduce the electrostatic repulsion between the hydrophilic groups of ammonium dodecyl sulfate, making the aggregation and arrangement of the hydrophilic groups at the air-liquid interface more compact and orderly, further reducing the area that air can contact with the solution surface, and reducing the surface tension of the composite solution more significantly. Therefore, the calcium chloride added in this patent can not only be used as an antifreeze agent, but also as an efficient inorganic salt additive for ammonium dodecyl sulfate in the composite solution, so that the composite solution has an excellent wetting effect.
[0067] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a composite antifreeze type microwave modified polymer dust suppressant, characterized in that: Prepare according to the following steps: (1) placing sodium alginate and sodium carboxymethyl starch in a container, heating them to uniformly disperse them in water, adding tert-butyl hydroperoxide solution, stirring, then adding N,N′-methylenebisacrylamide and acrylamide, placing the container in a microwave reactor, stirring and heating to react to obtain a uniform and stable sodium alginate-sodium carboxymethyl starch mixed solution; (2) cooling the sodium alginate-sodium carboxymethyl starch mixed solution, adding carboxymethyl chitosan and ammonium dodecyl sulfate, stirring thoroughly, adding calcium chloride, and mixing to obtain a composite antifreeze type microwave modified polymer dust suppressant.
2. The method for preparing the composite antifreeze type microwave modified polymer dust suppressant according to claim 1, characterized in that: In the composite antifreeze type microwave modified polymer dust suppressant reaction liquid, the mass concentration of sodium alginate is 0.25-0.45%, the mass concentration of sodium carboxymethyl starch is 0.05-0.09%, the mass concentration of tert-butyl hydroperoxide is 0.03-0.06%, the mass concentration of N,N′-methylenebisacrylamide is 0.02-0.03%, the mass concentration of acrylamide is 0.32-0.53%, the mass concentration of carboxymethyl chitosan is 0.19-0.39%, the mass concentration of calcium chloride is 0.62-1.17%, and the mass concentration of ammonium dodecyl sulfate is 0.02-0.03%.
3. The method for preparing the composite antifreeze type microwave modified polymer dust suppressant according to claim 2, characterized in that: The mass ratio of sodium alginate to sodium carboxymethyl starch is 5:
1.
4. The method for preparing the composite antifreeze type microwave modified polymer dust suppressant according to claim 3, characterized in that: The mass percentage content of tert-butyl hydroperoxide in the tert-butyl hydroperoxide solution is 30%.
5. The preparation of the composite antifreeze type microwave modified polymer dust suppressant according to claim 4, characterized in that: In step (1), the temperature for heating and dispersing is 60-70°C.
6. The method for preparing the composite antifreeze type microwave modified polymer dust suppressant according to claim 4, characterized in that: The microwave reactor was set to a reaction temperature of 40-50°C and a reaction time of 30-40 min.
7. The method for preparing the composite antifreeze type microwave modified polymer dust suppressant according to claim 6, characterized in that: After adding tert-butyl hydroperoxide solution, stir for 20-30 minutes.
8. A composite antifreeze type microwave modified polymer dust suppressant prepared by the preparation method of the composite antifreeze type microwave modified polymer dust suppressant according to any one of claims 1 to 7.
9. Use of the composite antifreeze type microwave modified polymer dust suppressant according to claim 8 in the prevention and control of coal dust in mining processes.
Citation Information
Patent Citations
Coal dust suppressor
CN104087251A
Composite coal dust inhibitor and preparation method thereof
CN108795385A